Toxicity of cypermethrin on the neotropical lacewing chrysoperla externa (neuroptera: chrysopidae) - Haramboure, Marina (2013)
The generalist predator Chrysoperla externa (Neuroptera: Chrysopidae) is distributed in the Neotropical Region and presents a strong potential as a biological control agent due to its easily rearing, high voracity and tolerance to several pesticides. This specie fed on relevant pests such as aphids, whiteflies, trips and various lepidopterans. In Argentina, an indiscriminate chemical control with broad spectrum pesticides is still the first option for controlling pests causing resistance problems and reduction of beneficial organisms. Therefore, it would be desirable that predators or parasitoids develop tolerance or resistance as phytophagous pests for their maintenance in the agricultural ecosystems. The objective of this work was to evaluate the tolerance of C. externa to the pyrethroid cypermethrin by topical exposure in laboratory conditions. The symptoms evaluated were tremors, movement, knockdown, inability to walk due to being glued. Recovery form poisoning symptoms was also evaluated. Six different concentrations of the pesticide, including the full field one, were tested. The exposure method was by topical applications on third larval instar. A low toxicity on larvae at 24 h post-treatment was observed, even at the highest concentration evaluated. Most of treated individuals looked normal at 24 h post-treatment; those who were knocked down showed a complete recovery between 48 and 72 h post-treatment. C. externa demonstrated a high tolerance to pyrethroids. This could be due to the activity involved in pyrethroids biotransformation (for example, esterases and mixed-function oxidases), or to a low sensitivity of the molecular target. Future studies should be addressed at biochemical and molecular levels to complete our knowledge about insecticides effects on this predator.